Phonetics and Phonology in Language Comprehension and Production 2003
DOI: 10.1515/9783110895094.115
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the relation between the production and recognition of spoken word forms

Abstract: In de spraak vinden het gemoeds-en het verstandsleven, beide, den klaarsten vorm van uitdrukking, die wederkeerig op de ontwikkeling van beide krachtig terugwerkt [In speech, our emotional and intellectual lives find their clearest form of expression, which in turn forcefully feeds back on the development of both] (Donders 1870: 10)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 85 publications
1
22
2
Order By: Relevance
“…However, assuming that the same concepts and linguistic representations are used in language comprehension and production (Roelofs, 2003), the problem of how idioms are represented in the mental lexicon is shared by both theories of comprehension and production. And indeed, the superlemma model can also be read, from input to concepts, as an account of idiom comprehension.…”
Section: Resultsmentioning
confidence: 99%
“…However, assuming that the same concepts and linguistic representations are used in language comprehension and production (Roelofs, 2003), the problem of how idioms are represented in the mental lexicon is shared by both theories of comprehension and production. And indeed, the superlemma model can also be read, from input to concepts, as an account of idiom comprehension.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, some imaging evidence suggests that different parts of Wernicke's area are involved in production and perception (Wise et al, 2001). If phonological input and output networks are separate but tightly connected, then activation of one phonological network would lead to the activation of the other, explaining the co-activation in imaging studies (Roelofs, 2003b).…”
Section: Evidence For Cross-talk Between Planning and Recognitionmentioning
confidence: 99%
“…In fact, on the basis of reviews of the literature, Monsell (1987) and Roelofs (2003b) concluded that the position of two linked systems best explains the available data. Given that some studies have suggested some influences from planning on recognition, the question arises about why links from production to perception would exist in separate but closely linked systems.…”
Section: Evidence For Cross-talk Between Planning and Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…My first major point was that the lexical and mixed error biases and the mixed distractor latency effect do not specifically support production-internal feedback, contrary to what Rapp and Goldrick (2000) maintained. I showed that a model with comprehension-based rather than production-internal feedback, namely WEAVERϩϩ (e.g., Levelt, Roelofs, & Meyer, 1999;Roelofs, 1992Roelofs, , 1997Roelofs, , 2003aRoelofs, , 2003bRoelofs & Hagoort, 2002), accounts for the error and latency findings. My second major point was that extant productioninternal feedback accounts of the error biases and latency effects are incompatible.…”
mentioning
confidence: 98%